Synchronization and Stability of Surface Acoustic Wave (SAW) Coupled Phase Oscillators and Sensing Applications - Jha, Shashank S.; Yadava, R.D.S. (Journal of Applied Nonlinear Dynamics, 2026)
We present an analysis of phase dynamics of two coupled limit cycle oscillators where coupling is provided by a simple surface acoustic wave (SAW) delay line and the coupled oscillators are either SAW delayed or direct self-feedback type. Synchronization and stability analyses are carried out with primary motivation to explore whether coupling SAW device in synchronization mode could make better sensing platform compared to usual SAW feedback oscillator. Also, the parametric dependencies of the phase dynamics are analyzed to determine whether SAW-coupled oscillators could become stable chaotic code generators for secure communication. Both limit cycle and chaotic dynamics are seen to occur in different regions of parametric space. It is found that by proper tuning of system parameters sensitivity can be enhanced by several orders of magnitude resulting in possibility for making advanced SAW sensor system.